Synthesis of multiply fluorinated N-acetyl-D-glucosamine and D-galactosamine analogs via the corresponding deoxyfluorinated glucosazide and galactosazide phenyl thioglycosides - Hamala, Vojtěch; Červenková Šťastná, Lucie; Kurfiřt, Martin; Cuřínová, Petra; Dračínský, Martin; Karban, Jindřich (Beilstein Journal of Organic Chemistry, 2021)
Multiple fluorination of glycostructures has emerged as an attractive way of modulating their protein affinity, metabolic stability, and lipophilicity. Here we described the synthesis of a series of mono-, di- and trifluorinated N-acetyl-ᴅ-glucosamine and ᴅ-galactosamine analogs. The key intermediates are the corresponding multiply fluorinated glucosazide and galactosazide thioglycosides prepared from deoxyfluorinated 1,6-anhydro-2-azido-β-ᴅ-hexopyranose precursors by ring-opening reaction with phenyl trimethylsilyl sulfide. Nucleophilic deoxyfluorination at C4 and C6 by reaction with DAST, thioglycoside hydrolysis and azide/acetamide transformation completed the synthesis.
Keywords: amino sugars; deoxyfluorination; fluorinated carbohydrates; hexosamine hemiacetals; thioglycosides

(untitled) - Linclau, B.; Ardá, A.; Reichardt, N.-C.; Sollogoub, M.; Unione, L.; Vincent, S. P.; Jiménez-Barbero, J. (Chem. Soc. Rev., 2020)

(untitled) - Williams, S. J.; Withers, S. G. (Carbohydr. Res., 2000)

Biomedical Frontiers of Fluorine Chemistry - Namchuk, M.; Braun, C.; McCarter, J. D.; Withers, S. G. (Fluorinated sugars as probes of glycosidase mechanisms, 1996)

(untitled) - Williams, D. A.; Pradhan, K.; Paul, A.; Olin, I. R.; Tuck, O. T.; Moulton, K. D.; Kulkarni, S. S.; Dube, D. H. (Chem. Sci., 2020)

(untitled) - Glaudemans, C. P. J.; Kováč, P.; Nashed, E. M. (Methods Enzymol., 1994)

(untitled) - Valverde, P.; Quintana, J. I.; Santos, J. I.; Ardá, A.; Jiménez-Barbero, J. (ACS Omega, 2019)

(untitled) - Gimeno, A.; Valverde, P.; Ardá, A.; Jiménez-Barbero, J. (Curr. Opin. Struct. Biol., 2020)

(untitled) - Biffinger, J. C.; Kim, H. W.; DiMagno, S. G. (ChemBioChem, 2004)

(untitled) - van Straaten, K. E.; Kuttiyatveetil, J. R. A.; Sevrain, C. M.; Villaume, S. A.; Jiménez-Barbero, J.; Linclau, B.; Vincent, S. P.; Sanders, D. A. R. (J. Am. Chem. Soc., 2015)

(untitled) - Dohi, H.; Périon, R.; Durka, M.; Bosco, M.; Roué, Y.; Moreau, F.; Grizot, S.; Ducruix, A.; Escaich, S.; Vincent, S. P. (Chem. – Eur. J., 2008)

(untitled) - Thanna, S.; Lindenberger, J. J.; Gaitonde, V. V.; Ronning, D. R.; Sucheck, S. J. (Org. Biomol. Chem., 2015)

(untitled) - Vermersch, P. S.; Tesmer, J. J. G.; Quiocho, F. A. (J. Mol. Biol., 1992)

(untitled) - Denavit, V.; Lainé, D.; St-Gelais, J.; Johnson, P. A.; Giguère, D. (Nat. Commun., 2018)

(untitled) - St-Gelais, J.; Bouchard, M.; Denavit, V.; Giguère, D. (J. Org. Chem., 2019)

(untitled) - St‐Gelais, J.; Côté, É.; Lainé, D.; Johnson, P. A.; Giguère, D. (Chem. – Eur. J., 2020)

(untitled) - Linclau, B.; Wang, Z.; Compain, G.; Paumelle, V.; Fontenelle, C. Q.; Wells, N.; Weymouth-Wilson, A. (Angew. Chem., Int. Ed., 2016)

(untitled) - Johannes, M.; Reindl, M.; Gerlitzki, B.; Schmitt, E.; Hoffmann-Röder, A. (Beilstein J. Org. Chem., 2015)

(untitled) - Sun, X.-L.; Kanie, Y.; Guo, C.-T.; Kanie, O.; Suzuki, Y.; Wong, C.-H. (Eur. J. Org. Chem., 2000)

(untitled) - Axer, A.; Jumde, R. P.; Adam, S.; Faust, A.; Schäfers, M.; Fobker, M.; Koehnke, J.; Hirsch, A. K. H.; Gilmour, R. (Chem. Sci., 2021)

(untitled) - Malassis, J.; Vendeville, J.-B.; Nguyen, Q.-H.; Boujon, M.; Gaignard-Gaillard, Q.; Light, M.; Linclau, B. (Org. Biomol. Chem., 2019)

(untitled) - Bresciani, S.; Lebl, T.; Slawin, A. M. Z.; O'Hagan, D. (Chem. Commun., 2010)

(untitled) - Sharma, M.; Bernacki, R. J.; Paul, B.; Korytnyk, W. (Carbohydr. Res., 1990)

(untitled) - Werz, D. B.; Ranzinger, R.; Herget, S.; Adibekian, A.; von der Lieth, C.-W.; Seeberger, P. H. (ACS Chem. Biol., 2007)

(untitled) - Fu, C.; Zhao, H.; Wang, Y.; Cai, H.; Xiao, Y.; Zeng, Y.; Chen, H. (HLA, 2016)

(untitled) - Berkin, A.; Szarek, W. A.; Kisilevsky, R. (Carbohydr. Res., 2000)

(untitled) - Horník, Š.; Červenková Šťastná, L.; Cuřínová, P.; Sýkora, J.; Káňová, K.; Hrstka, R.; Císařová, I.; Dračínský, M.; Karban, J. (Beilstein J. Org. Chem., 2016)

(untitled) - Morrison, Z. A.; Nitz, M. (Carbohydr. Res., 2020)

(untitled) - Hough, L.; Penglis, A. A. E.; Richardson, A. C. (Can. J. Chem., 1981)

(untitled) - Sharma, M.; Bernacki, R. J.; Hillman, M. J.; Korytnyk, W. (Carbohydr. Res., 1993)

(untitled) - Wasonga, G.; Tatara, Y.; Kakizaki, I.; Huang, X. (J. Carbohydr. Chem., 2013)

(untitled) - Wagner, S.; Mersch, C.; Hoffmann-Röder, A. (Chem. – Eur. J., 2010)

(untitled) - Mersch, C.; Wagner, S.; Hoffmann-Röder, A. (Synlett, 2009)

(untitled) - Johannes, M.; Oberbillig, T.; Hoffmann-Röder, A. (Org. Biomol. Chem., 2011)

(untitled) - Stephenson, E. L.; Zhang, P.; Ghorbani, S.; Wang, A.; Gu, J.; Keough, M. B.; Rawji, K. S.; Silva, C.; Yong, V. W.; Ling, C.-C. (ACS Cent. Sci., 2019)

(untitled) - Nishimura, S.-I.; Hato, M.; Hyugaji, S.; Feng, F.; Amano, M. (Angew. Chem., Int. Ed., 2012)

(untitled) - van Wijk, X. M.; Lawrence, R.; Thijssen, V. L.; van den Broek, S. A.; Troost, R.; van Scherpenzeel, M.; Naidu, N.; Oosterhof, A.; Griffioen, A. W.; Lefeber, D. J.; van Delft, F. L.; van Kuppevelt, T. H. (FASEB J., 2015)

(untitled) - Keough, M. B.; Rogers, J. A.; Zhang, P.; Jensen, S. K.; Stephenson, E. L.; Chen, T.; Hurlbert, M. G.; Lau, L. W.; Rawji, K. S.; Plemel, J. R.; Koch, M.; Ling, C.-C.; et al. (Nat. Commun., 2016)

(untitled) - Qin, K.; Zhang, H.; Zhao, Z.; Chen, X. (J. Am. Chem. Soc., 2020)

(untitled) - Wang, L.-X.; Sakairi, N.; Kuzuhara, H. (J. Chem. Soc., Perkin Trans. 1, 1990)

(untitled) - Kurfiřt, M.; Červenková Št’astná, L.; Dračínský, M.; Müllerová, M.; Hamala, V.; Cuřínová, P.; Karban, J. (J. Org. Chem., 2019)

(untitled) - Lin, P.-C.; Adak, A. K.; Ueng, S.-H.; Huang, L.-D.; Huang, K.-T.; Ho, J.-a. A.; Lin, C.-C. (J. Org. Chem., 2009)

Timely Research Perspectives in Carbohydrate Chemistry - Dax, K.; Albert, M.; Hammond, D.; Illaszewicz, C.; Purkarthofer, T.; Tscherner, M.; Weber, H. (Rearrangements in the Course of Fluorination by Diethylaminosulfur Trifluoride at C-2 of Glycopyranosides: Some New Parameters, 2002)

(untitled) - Karban, J.; Císařová, I.; Strašák, T.; Šťastná, L. Č.; Sýkora, J. (Org. Biomol. Chem., 2012)

(untitled) - Lainé, D.; Denavit, V.; Lessard, O.; Carrier, L.; Fecteau, C.-É.; Johnson, P. A.; Giguère, D. (Beilstein J. Org. Chem., 2020)

(untitled) - Quiquempoix, L.; Wang, Z.; Graton, J.; Latchem, P. G.; Light, M.; Le Questel, J.-Y.; Linclau, B. (J. Org. Chem., 2019)

(untitled) - Baer, H. H.; Mateo, F. H.; Siemsen, L. (Carbohydr. Res., 1989)

(untitled) - Popsavin, V.; Benedeković, G.; Popsavin, M.; Divjaković, V.; Armbruster, T. (Tetrahedron, 2004)

(untitled) - Chen, S. Y.; Joullie, M. M. (J. Org. Chem., 1984)

(untitled) - Vera-Ayoso, Y.; Borrachero, P.; Cabrera-Escribano, F.; Gómez-Guillén, M. (Tetrahedron: Asymmetry, 2005)

(untitled) - Vera-Ayoso, Y.; Borrachero, P.; Cabrera-Escribano, F.; Carmona, A. T.; Gómez-Guillén, M. (Tetrahedron: Asymmetry, 2004)

(untitled) - Suzuki, K.; Ito, Y.; Kanie, O. (Carbohydr. Res., 2012)

(untitled) - Herczeg, M.; Mező, E.; Eszenyi, D.; Lázár, L.; Csávás, M.; Bereczki, I.; Antus, S.; Borbás, A. (Eur. J. Org. Chem., 2013)

(untitled) - Card, P. J.; Reddy, G. S. (J. Org. Chem., 1983)

(untitled) - Kolakowski, R. V.; Shangguan, N.; Sauers, R. R.; Williams, L. J. (J. Am. Chem. Soc., 2006)

(untitled) - Dhakal, B.; Crich, D. (J. Am. Chem. Soc., 2018)

(untitled) - Wray, V. (J. Chem. Soc., Perkin Trans. 2, 1976)

(untitled) - Phillips, L.; Wray, V. (J. Chem. Soc. B, 1971)

(untitled) - Denavit, V.; Lainé, D.; Bouzriba, C.; Shanina, E.; Gillon, É.; Fortin, S.; Rademacher, C.; Imberty, A.; Giguère, D. (Chem. – Eur. J., 2019)